2012
DOI: 10.1007/s00705-012-1529-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the recent outbreak of foot-and-mouth disease virus serotype SAT2 in Egypt

Abstract: An outbreak of foot-and-mouth disease (FMD) in Egypt affected approximately 40,000 cattle and water buffaloes and killed more than 4,600 animals during February-March 2012. To investigate the etiology of the 2012 outbreak, specimens were collected from six governorates and analyzed using universal primers to amplify the 5' untranslated region (UTR) by reverse-transcription polymerase chain reaction. Only FMDV-SAT2 was detected, with an overall detection rate of 80.3 %. Complete VP1- and leader-proteinase-codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 27 publications
5
45
0
1
Order By: Relevance
“…FMD is generally a disease that causes high morbidity and low mortality. However, there are sporadic reports of FMD outbreaks with unusually high mortality rates [[1],[2]], with fatalities often being attributed FMDV-associated myocarditis (as reviewed by [[3]]). Investigations based on specimens obtained from field outbreaks [[2],[4]], as well as experimental studies [[5],[6]], have confirmed a relationship between acute FMDV infection and fatal myocarditis in young ruminants and pigs.…”
Section: Introductionmentioning
confidence: 99%
“…FMD is generally a disease that causes high morbidity and low mortality. However, there are sporadic reports of FMD outbreaks with unusually high mortality rates [[1],[2]], with fatalities often being attributed FMDV-associated myocarditis (as reviewed by [[3]]). Investigations based on specimens obtained from field outbreaks [[2],[4]], as well as experimental studies [[5],[6]], have confirmed a relationship between acute FMDV infection and fatal myocarditis in young ruminants and pigs.…”
Section: Introductionmentioning
confidence: 99%
“…For the virus to escape from sub-Saharan Africa four times in 1 year is unprecedented, and it has been suggested that the political changes in the region from 2011 onwards (the “Arab Spring”) may have played a role (), as people and their animals were displaced by conflict or changing governments created new trading relationships and thus new pathways for pathogens to follow. For example, Kandeil et al (8) note that cattle imports to Egypt from other countries in the Nile basin increased following the Egyptian revolution of 2011 due to improved political relationships between the governments involved.…”
Section: Introductionmentioning
confidence: 99%
“…Due to low meat production and high prices of local animals, Egyptian authorities resort to importing livestock animals to fill the gap between production and consumption. As a result of supporting political relations between Egypt and the Nile Basin countries during last year, the importing of live animals increased slightly, especially from Sudan and Ethiopia (Kandeil et al, 2013;EL-Bayoumy et al, 2014). There is no organized FMD control strategy in some African countries from which Egypt import live cattle except sporadic cattle herd vaccination usually after outbreaks (Jibat et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…There is no organized FMD control strategy in some African countries from which Egypt import live cattle except sporadic cattle herd vaccination usually after outbreaks (Jibat et al 2013). In 2006, Egypt experienced a major FMD outbreak, resulting in the loss of nearly one million head of cattle (Kandeil et al, 2013). This outbreak was caused by a FMDV serotype "A", which is closely related to FMDV serotype A21 Kenya, shortly after importing of live cattle from Ethiopia and both imported and local breeds expressed the disease (El-Kholy et al, 2007).…”
Section: Resultsmentioning
confidence: 99%